Оценка адаптивности регуляторов мощности дуговых сталеплавильных печей к внешним возмущениям - Панкратов, Анатолий Иванович; Афанасьева, Анастасия Владимировна (НТУ "ХПИ", 2010)
An article is devoted to diagnostic of adaptability of various power regulators used at arc steel furnaces to external disturbances in power circuits. The models of power circuits of an arc furnace with disturbances and with different power regulators were created. According to research it was found impedance regulator has the greatest adaptability to the external disturbances. The diagnostic of impact of the disturbances in power circuit of the arc steel furnace will improve the quality of power regulation and therefore increase the productivity of the furnace.
The diagnostic of adaptability of power regulators of arc steel furnaces to external disturbances
Keywords: металлургия черная; производство сталеплавильное; регулирование автоматическое; мощность; регулятор токовый; регулятор дифференциальный; регулятор импедансный